Action-research restoration trials, Marsabit and Isiolo counties, Kenya - Ng'ang'a, Irene N.; Flintan, Fiona E.; Sircely, Jason A. (International Livestock Research Institute, 2023)
The International Livestock Research Institute (ILRI), in partnership with African Medical and Research Foundation (Amref) and Veterinaires Sans Frontiere (VSF) Suisse, are jointly implementing HEAL (One Health for Humans, Environment, Animals and Livelihood in parts of Kenya, Ethiopia and Somalia. ILRI is implementing the rangeland health component. The restoration strategy outlined here focuses on action research trials using collaboratively designed restoration protocols, managed by livestock producers. These trials serve to document quantitative restoration effects, providing clear demonstrations to pastoralist producers for knowledge and capacity building. Moreover, action research trials offer essential ground data for monitoring and evaluating both small- scale restoration initiatives and large-scale management, facilitated by connections to remote sensing methodologies. For more impactful restoration efforts, intensive and targeted interventions are most effective when built on the existing foundation of local grazing management systems designed and implemented by community institutions of livestock keepers.